A survey of Japanese mothers on the effectiveness of the Ministry of Health, Labor and Welfare's revised HPV vaccine leaflet. Issue 10 (2nd October 2020) - Shiomi, Mayu; Ueda, Yutaka; Abe, Hazuki; Yagi, Asami; Sakiyama, Kanako; Kimura, Tadashi; Tanaka, Yoshimichi; Ohmichi, Masahide; Ichimura, Tomoyuki; Sumi, Toshiyuki; Murata, Hiromi; Okada, Hidetaka; et al.
ABSTRACT: Introduction : In June of 2013, Japan's Ministry of Health, Labor and Welfare (MHLW) suspended its position of strong recommendation for the routine immunization of young girls against the Human Papilloma Virus (HPV) because of reports of adverse reactions after the vaccination. For the next four years, the MHLW's website warned about the significance of these adverse events. In January of 2018, MHLW's website was modified to reflect a less negative stance. We have studied public awareness of MHLW's revised leaflet in Japanese women whose daughters were of the targeted age for receiving the HPV vaccine and how this awareness influenced their intentions to get their daughters vaccinated. Materials and Methods : From June to December of 2018, a survey was conducted through the Departments of Obstetrics and Gynecology at 14 different medical facilities. The questionnaire was distributed to women whose daughters were of the HPV–vaccine-targeted age. The survey measured their responses before and after being presented with the 2018-revised MHLW leaflet. Responses from 384 mothers were analyzed. Results : Before being presented with the leaflet, the survey found that the percentage of responder's daughters already vaccinated was 6.5% (24/372). After reading the MHLW leaflet, an additional 6.9% (24/346) responded "I want to get my daughter vaccinated immediately", and 37.6% (130/346) responded "I have positive feelings about HPV vaccination". Discussion : By presenting the new MHLW leaflet at obstetrics and gynecology facilities, we expect to be able to effectively increase the HPV vaccination rate in Japan.